CTPS Intervention as an Effort to Prevent Diarrhea in the Kaledupa Community Health Center Work Area, Wakatobi - Syaputri, Fatjrina; Solihin, Solihin; Serli, Serli (Universitas Mandala Waluya, 2025)
Diarrhea remains a public health problem in the Kaledupa Community Health Center working area, affecting 35.7% of the population. There have been fluctuations in the incidence of diarrhea from year to year. In 2021, there were 2,774 cases of diarrhea in Wakatobi District. One of the factors contributing to the high incidence of diarrhea is poor hand washing with soap (HWS/CTPS). This study aims to analyze the relationship between HWS practices and the incidence of diarrhea before and after health education interventions. This is a quantitative study with a cross-sectional design. The population consists of the entire community in the Kaledupa Community Health Center working area, totaling 5,865 people, with a sample of 99 respondents determined using the Slovin formula and proportional random sampling technique. Data were collected through a structured questionnaire. The post-test also found a significant relationship. Respondents with good HWS practices experienced diarrhea less frequently than respondents with poor HWS practices. It was concluded that health education interventions using pamphlets were effective in increasing community knowledge about HWS practices and as an effort to reduce the incidence of diarrhea. It is recommended that the Kaledupa Community Health Center continue to strengthen health promotion programs such as counseling and demonstrations related to CTPS, provide CTPS facilities and infrastructure, and involve families and the community in daily CTPS practices.